Green synthesis of phloroglucinol-urotropine porous polymer: Ingenious miniaturized solid phase extraction for efficient purification and determination of polycyclic aromatic hydrocarbons in lotus roots. (1st December 2022) - Zhai, Chengcheng; Wang, Mingwei; Lu, Yanke; Yan, Hongyuan
Highlights : A fluffy phloroglucinol-urotropine porous polymer (PU-PP) was synthesized. Miniaturized pipette tip solid phase extraction (PT-SPE) required only 3 mg PU-PP. A PU-PP-PT-SPE-HPLC for simultaneous determination of four PAHs was developed. The PU-PP-PT-SPE-HPLC method showed good practicability in lotus root samples. Abstract: Polycyclic aromatic hydrocarbons (PAHs) posed a serious threat to food safety and human health due to long-term emission. In this work, a new method was established using phloroglucinol-urotropine porous polymer (PU-PP) in a pipette tip for solid phase extraction (PT-SPE) for the first time and used prior to determination of four PAHs (phenanthrene, anthracene, fluoranthene, and pyrene) in lotus roots. Synthesis of the PU-PP adsorbent was green compared with alternatives; urotropine was used as a cross-linker and ethanol–water as the solvent. PU-PP-based PT-SPE had the advantages of low solvent consumption, good purification, practicability, stability, and low-cost. The proposed pre-purification method offered low limits of detection (0.09–0.28 ng/g) and good recoveries (84.6–114.3 %, RSDs ≤ 5.6 %) for determination of the four PAHs, which were detected at trace concentrations in samples. This new method provides an alternative for monitoring trace pollutants in aquatic plant ingredients.